2011
DOI: 10.1143/ptp.125.537
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Breaking of the Rotational Symmetry in Dimensionally Reduced Super Yang-Mills Models

Abstract: We investigate the spontaneous breaking of the SO(D) symmetry in matrix models, which can be obtained by the zero-volume limit of pure SU(N ) super Yang-Mills theory in D = 6, 10 dimensions. The D = 10 case corresponds to the IIB matrix model, which was proposed as a non-perturbative formulation of type IIB superstring theory, and the spontaneous breaking corresponds to the dynamical compactification of space-time suggested in that model. First we study the D = 6 case by the Gaussian expansion method, which tu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
38
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 25 publications
(49 citation statements)
references
References 33 publications
10
38
1
Order By: Relevance
“…In this paper, we extend this work to the 6D version of the type IIB matrix model, which can be obtained by dimensionally reducing 6D super Yang-Mills theory to a point in the same way as one obtains the type IIB matrix model by dimensionally reducing 10D super Yang-Mills theory. The 6D version also suffers from the sign problem due to a complex determinant, which appears after integrating out the fermionic matrices, and its phase is speculated to cause the SSB of SO(6) rotational symmetry to SO(3) according to the GEM [34]. We show that the CLM indeed enables us to address this issue from first principles with the aid of the deformation technique, and our results turn out to be consistent with those of the GEM.…”
Section: Introductionsupporting
confidence: 73%
“…In this paper, we extend this work to the 6D version of the type IIB matrix model, which can be obtained by dimensionally reducing 6D super Yang-Mills theory to a point in the same way as one obtains the type IIB matrix model by dimensionally reducing 10D super Yang-Mills theory. The 6D version also suffers from the sign problem due to a complex determinant, which appears after integrating out the fermionic matrices, and its phase is speculated to cause the SSB of SO(6) rotational symmetry to SO(3) according to the GEM [34]. We show that the CLM indeed enables us to address this issue from first principles with the aid of the deformation technique, and our results turn out to be consistent with those of the GEM.…”
Section: Introductionsupporting
confidence: 73%
“…From the intersecting point, we can obtain the extent of spacetime in the shrunken directions. We find that it is given by x ∼ 0.35, which should be compared with the value obtained by the Gaussian expansion method [19] …”
Section: Euclidean Type Iib Matrix Modelsupporting
confidence: 48%
“…The Gaussian expansion method has been applied also to a 6d version of the type IIB matrix model, which can be obtained by dimensionally reducing 6d super Yang-Mills (SYM) theory to a point [19], and it was found that the SO(6) symmetry is spontaneously broken down to SO(3). The mechanism of SSB is demonstrated by Monte Carlo studies in this case [20].…”
Section: Euclidean Type Iib Matrix Modelmentioning
confidence: 99%
“…25 There the value of the free energy tends to decrease slightly as one goes from order 3 to order 5. Considering such artifacts due to truncation, we speculate that the Krauth-Nicolai-Staudacher conjecture 24 actually refers to the partition function for the SO(10) symmetric vacuum (see Fig.…”
Section: Defining the Lorentzian Matrix Modelmentioning
confidence: 97%